Pneumatosis cystoidis intestinalis presenting as bowel perforation, a rare entity - Hanna, Philippe (Int J Surg Case Rep, 2016)
INTRODUCTION: Pneumatosis cystoides intestinalis (PCI) is an uncommon condition. This following article describes a case of primary PCI presenting as acute abdomen due to perforation of a small bowel cyst. PRESENTATION OF CASE: This following article describes the case of an 88 year-old woman admitted at the hospital with peritonitis and consequently operated for a presumed bowel ischemia and perforation. However surgical exploration revealed perforated PCI. DISCUSSION: The pathophysiology of secondary PCI is poorly understood. Gas produced by Gas-forming bacteria may enter the mucosal barrier due and consequently this gas accumulates within the bowel wall. Also malnutrition can prevent the digestion of carbohydrates, which leads to increased bacterial fermentation, and production of large volumes of gas leading to distention and ischemia and subsequently the submucosal dissection of gas. Colonoscopy is helpful in excluding other colonic lesions and it shows the submucosal cysts that have a typical dual appearance: multiple white small cysts coupled to a sub-atrophic mucosa or larger cysts (up to 3 cm) with a reddened overlying mucosa. CONCLUSION: The treatment unless complicated should be conservative even in the presence of pneumoperitoneum, after excluding complications.